Assessment of the status of wetlands based on the integration of space and terrestrial information (by the example of the upper Kiev reservoir) - Tomchenko, O.V.; Fedorovsky, A.D. (Reports of the National Academy of Sciences of Ukraine, 2017)
The ways of improving the methodological provision of a space geominotoring of the state of wetlands based on the integration of remote sensing data and ground observations by developing the proper mathematical models of system analysis and the formation of generalizing criteria (the evidence from the upper Kyiv reservoir) are studied.